Signatures of equatorial electrojet in the mesospheric partial reflection drifts over magnetic equator - Gurubaran, S.; Rajaram, R. (My University, 2000)
The partial reflection (PR) drifts at 98 km measured by the medium frequency (MF) radar operating at Tirunelveli, India, situated close to the magnetic equator, are shown to have the combined effects of mesospheric winds and the equatorial electrojet. The evidences for this behavior of the PR drifts are brought out from a detailed examination of the temporal variation of the dynamical and the geometrical parameters associated with the ground diffraction pattern.
Keywords: Magnetic equator; Equatorial electrojet; Mesosphere-ionosphere coupling; Mesospheric dynamics; Partial reflection drifts